Anomalous ichthyoplankton distributions and concentrations in the northern California Current during the 2010 El Niño and La Niña events. (September 2015) - Auth, Toby D.; Brodeur, Richard D.; Peterson, Jay O.
Highlights: 2010 El Niño to La Niña transition resulted in anomalous fish larvae off OR and WA. More larvae off Oregon in winter 2010 than in any other year from 1998 to 2011. More larvae in May 2010 than during any May from 2004 to 2009 and 2011. Ekman transport, Columbia River, upwelling, chlorophyll, PDO related to anomalies. Abstract: In late spring of 2010, the northern California Current (NCC) experienced a transition from El Niño to La Niña conditions resulting in anomalous distributions and concentrations within the ichthyoplankton community. We analyzed larval fish data collected during the four months before and after this transition and compared them to data from three previous studies conducted in the NCC. In one comparison, concentrations of larvae collected during winter from stations 2 to 46 km offshore along the central Oregon coast were higher in 2010 than in any other year from 1998 to 2011. In a second comparison of nearshore larvae collected during six periods (1971–1972, 1978, 1983, 1998, 1999–2002, and 2003–2005) previous to 2010, concentrations of total larvae and most dominant larval taxa were higher during the winter/spring and lower during the summer/fall seasons in 2010 (corresponding to the shift from El Niño to La Niña conditions) than during similar seasons in any other annual period. In a third comparison, larvae collected from stations 21 to 102 km offshore along the southern Washington to south-central Oregon coast in May 2010, at the end of the El Niño event, were found in higher concentrations than during any May from 2004 to 2009 and 2011. The high concentration of larvae in the winter and spring of 2010 was likely the direct result of El Niño and warm-ocean conditions (high values of the MEI, NOI, and PDO) along with strong downwelling and onshore transport that increased the abundance of offshore taxa over the shelf. Continued monitoring of the NCC is warranted as El Niño effects on larval fish observed in the past may not be indicative of future effects.